Face-to-face modality students' perceptions on online accounting learning: an analysis using SEM (Encuentros, 2022)
This paper aims to analyze the perceptions that the students of the face-to-face Public Accounting program of the Universidad Militar Nueva Granada in Bogotá hold about their learning and their satisfaction with using virtual learning environments. To that end, a sample of 106 students who had taken financial accounting courses was used. The variables selected for the analysis were 77 observable variables, four endogenous latent variables (satisfaction, student-student relationship, and professor-student relationship in two dimensions), and one exogenous latent variable (perceived learning). The modeling was done using the Structural Equation Model (SEM). Per our findings, the professor-student interaction in its two dimensions positively affects both perceived learning and student satisfaction, which does not occur with the student-student relationship. The main conclusion is that professor’s actions in virtual learning improve learning, but collaboration between students exerts no effect on their perceived learning.